Distributional Effects of Crises : The Role of Financial Transfers - Halac, Marina; Schmukler, Sergio L. (World Bank, Washington, DC, 2014)
Financial crises affect income distribution by way of different channels. The authors argue that financial transfers are an important channel which has been overlooked by the literature. They study the role of financial transfers by analyzing some of the most severe Latin American crises during the past decades (Chile 1981-83, Mexico 1994-95, Ecuador 1998-2000, Argentina 2001-02, and Uruguay 2002). First, the authors investigate transfers to the financial sector-those from nonparticipants to participants of the financial sector. Second, they explore who receives these financial transfers by identifying the winners and losers within the financial sector. Their analysis suggests that financial transfers during crises are large and expected to increase income inequality.